Incidence of Post-Operative Stricture Following Hepaticojejunostomy for Benign and Malignant Disease: Stricture Risk After Hepaticojejunostomy - Amin, Muhammad; Ullah, Misbah; Munir, Maryam; Ullah, Ishfaq (Pakistan Journal of Health Sciences, 2025)
Hepaticojejunostomy remains essential for biliary obstruction management, yet postoperative strictures significantly impact outcomes. Current incidence estimates (4-19%) vary widely due to methodological differences, and recent evidence questions the validity of the commonly referenced 12.5% benchmark used for study design. Objective: To: 1) determine contemporary stricture incidence using standardized criteria, 2) compare benign versus malignant cases, and 3) evaluate 3-month follow-up adequacy. Methods: A prospective cohort study was conducted involving 52 consecutive patients who underwent hepaticojejunostomy, with a mean age of 53.8 years (95% CI: 50.5–57.1). Strictures required both clinical (ICD-9 coding plus symptoms/biochemical evidence) and radiographic confirmation (CT/MR cholangiography). Statistical analyses included exact binomial CIs and chi-square tests (significance at p<0.05). Results: The overall stricture incidence was 19.2% (10/52, 95% CI: 9.6-32.5%). Benign cases showed significantly higher stricture rates (33.3% [8/24], 95% CI: 15.6-55.3%) versus malignant cases (7.1% [2/28], 95% CI: 0.9-23.5%; p=0.017). Conclusions: This study confirmed significantly higher stricture risk in benign disease and suggests current surveillance protocols may require pathology-specific modifications. The statistically significant association (p=0.017) between benign pathology and stricture formation underscores the need for risk-adapted management. Future research should prioritize multicenter cohorts with extended follow-up to validate these findings and refine surveillance guidelines.